Simultaneous pyometra and viable puppies’ gestation in a bitch - Risso, Analía Lorena (2014)
Here we describe a case of pyometra coexisting with gestation in a 4.5 year-old miniature short-haired Dachshund. The dog exhibited depression, vaginal discharge, polydipsia and dehydration. Ultrasound examination revealed the presence of low to moderate anechoic fluid collection in the left uterine horn. Blood analysis revealed mild neutrophilia with a left shift. Based on these findings a presumptive diagnosis of pyometra was made and the bitch was treated using amoxicillin-clavulanate with dopaminergic agonist (cabergoline). A second ultrasound scan revealed the presence of two gestational vesicles in the right uterine horn that were successfully carried to term. Unusually, while pyometra persisted in the left uterine horn, two viable puppies were delivered by caesarean section from the right uterine horn.